The Effect of Metal Oxide Content on Ash Fusion Temperature (AFT) and Determination of Coal Slagging and Fouling Indices - Rozaq, Muhammad Fat’hul (CV. Publikasi Indonesia, 2025)
One of the abundant natural resources on Earth is coal, and one of its main uses is as fuel. The utilization of coal as an industrial fuel produces waste in the form of coal ash. The oxide composition of coal ash significantly influences the fusion temperature of the sample, which, in turn, affects the formation of slagging and fouling. Therefore, it is necessary to investigate the oxide composition of coal ash and its effect on the ash fusion temperature (AFT), as well as to determine the slagging and fouling indices. In this study, coal ash was melted and subsequently analyzed for its oxide composition, tested for ash fusion temperature (AFT), and evaluated for slagging and fouling indices. The results showed that high SiO₂ content combined with low Al₂O₃, Fe₂O₃, CaO, and MgO contents tends to decrease the AFT value. However, when both SiO₂ and Al₂O₃ contents are high and Fe₂O₃, CaO, and MgO contents are low, the AFT tends to increase. Furthermore, if the Fe₂O₃, CaO, and MgO contents are slightly higher than those of SiO₂ and Al₂O₃, the AFT also tends to increase. The calculated slagging and fouling indices indicated that almost all samples fall within the high to very high categories. These findings provide practical guidance for coal-fired power plant operators in Indonesia to predict and mitigate ash-related operational challenges, particularly in boiler design optimization and fuel blending strategies to minimize slagging and fouling occurrences, thereby improving combustion efficiency and reducing maintenance costs.